Interleukin-6 as A Prognostic Biomarker in Perinatal Asphyxia - Boskabadi , Hassan; Maamouri, Gholamali; Zakerihamidi, Maryam; Bagheri, Fatemeh; Mashkani, Baratali; Mafinejad , Shahin; Faramarzi , Rahelah; Boskabadi , Abbas; Khodashenas , Ezzat; Heidari , Elaheh; Rakhshanizadeh , Forough (Iranian Journal of Child Neurology, 2021)
Abstract Objective Early diagnosis is considered as a priority for prevention and treatment of asphyxia-related complications. The main aim of the present study was to evaluate the prognostic value of interleukin-6 (IL-6) and hypoxic ischemic encephalopathy grade in prediction mortality and developmental status of neonates affected by prenatal asphyxia. Materials & Method The cohort study was conducted on 38 term asphyxiated infants at Ghaem hospital, Mashhad, Iran, during 2013-2017. The HIE grade and serum IL-6 levels were determined at the time of birth. The developmental status was determined using the Denver II test at the end of two-year follow-up. Results HIE grade 3 resulted in 83% mortality rate and developmental delay in all the survivors. The average IL-6 level was 2.7 ng/ml in the control group (not affected HIE) which increased up to 29, 175 and 136 ng/ml in those with HIE grades 1, 2 and 3, respectively. Roc curve analysis revealed the cut-off levels 24 pg/ml to predict the developmental delay with sensitivity and specificity of 96 and 92%, respectively. Conclusion The IL-6 level and HIE grade are the potential prognostic biomarkers for determination of mortality and morbidity rate in the asphyxiated neonates